Getting Physically Active by E-Bike: An Active Commuting Intervention Study - Thomas Mildestvedt; Olav Hovland; Sveinung Berntsen; Elling Bere; Liv Fegran (Physical Activity and Health, 2020)
Introduction: Increased physical activity (PA) is a major component in promoting public health, and active commuting could make an important contribution. Using an electric bicycle (e-bike) is reported to be of at least moderate intensity PA and is an alternative to other modes of transport for commuting. We aimed to explore the experience of commuting by e-bike in an intervention study. Methods: Focus group interviews with 21 previously inactive participants from three cities in Norway, who were given access to an e-bike for commuting for three (N = 2) or eight months (N = 19). Participants cycled for 226 days on average. The interviews were analyzed using systematic text condensation. Results: The use of e-bikes and active commuting stimulated some participants to take on additional PA in their leisure time. Others preferred active commuting to be their daily PA. Participants’ experiences of commuting by e-bike were characterized by a motivational shift from external reasons for e-biking, such as pressure to get fit, to feelings of well-being, enjoyment and recognition of the health benefits. Conclusion: Commuting by e-bike was convenient and promoted good health. Promoting e-bikes could lead to long term changes among inactive people because positive experiences stimulate autonomous reasons for active commuting.